Violin concerto by Gian Carlo Menotti: at the intersection of opera and instrumental genres - Antonova, Olena (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2022)
The relevance of the study is to study the instrumental works by G. С. Menotti, known worldwide primarily as an opera composer. His four concerts, unfortunately, did not receive such recognition as his operas, unfairly remaining in the shadow of the latter. The Violin Concerto, which was recorded only twice in the first 44 years after its premiere in 1952, is no exception. Performing interest in this work intensified in the late twentieth century, but scientific research is still isolated, and they do not cover the question: whether the interpretation of a purely instrumental genre influenced the opera aspirations and skills of the composer and if so, how? The main objective of the study is to trace the interaction of opera and instrumental principles in Menotti's Violin Concerto and to identify the peculiarities of the interpretation of the chosen genre due to such interaction. The methodology includes historical (to consider circumstances of the creation and the performance of the concerto), comparative (to identify common features in the theme and compositional organization of the concert and the opera "Amal and Night Guests"), as well as structuralfunctional, genre-style and intonational-dramatic methods (for a comprehensive analysis of the work). Results and conclusions. Menotti's Violin Concerto is considered in the aspect of opera influences due to the author's many years of experience in the field of theatrical music. The lack of dissemination of the work in the world of violin was stated, the names of its performers were given — from the premiere to the present. The structure and figurative content of the concert are characterized, the ratio of typical and atypical genre features is indicated, the presence of elements of end-to-end tonal and thematic development within the cycle is emphasized. The properties of music themes, which reflect the typical for Menotti operas mixed type of vocal intonation with a combination of cantilena and declamatory phrases, are analyzed. The figurative-thematic connection between the concert and opera works of the composer is traced, in particular, by comparing certain episodes of the Violin Concerto and the opera «Amal and Night Guests». Theatrical influences at the compositional and dramaturgical level, such as «cadre» fragmentation of sections and frequency of their changes in the opening and closing movements of the concert, proximity to the end-to-end opera stage in the middle part, are revealed. An analogy between the ratio of solo and orchestral parts in concert and in Menotti's operas is made. Emphasis is placed on the leading role of the violin solo in the concert, which is determined by the exposure of most music themes in its part, virtuosity of presentation, the presence of a large number of purely solo episodes, including two cadences. At the same time, it is noted that the originality of Menotti's concert is not only due to opera influences, but also to the dedicate the work for a specific performer — the American violinist Efrem Zimbalist. The close cooperation of the two musicians affected the character of the solo part in the concert and, indirectly, its music content.